Cyclical Patterns of Systemic Risk Metrics : Cross-Country Analysis. (IMF Working Papers; Working Paper ;, 2021)
We analyze a range of macrofinancial indicators to extract signals about cyclical systemic risk across 107 economies over 1995-2020. We construct composite indices of underlying liquidity, solvency and mispricing risks and analyze their patterns over the financial cycle. We find that liquidity and solvency risk indicators tend to be counter-cyclical, whereas mispricing risk ones are procyclical, and they all lead the credit cycle. Our results lend support to high-level accounts that risks were underestimated by stress indicators in the run-up to the 2008 global financial crisis. The policy implications of conflicting risk signals would depend on the phase of the credit cycle.